2018
DOI: 10.18551/rjoas.2018-07.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Funding and Investment Decisions Toward Company Value With Dividend Policy as the Intervening Variable on Manufacturing Sector Listed in Indonesia Stock Exchange

Abstract: Company value reflects the current value of the desired revenue in the future and the indicator for the market in assessing the company holistically. Implementing the financial management function is the way that can be done to achieve the company's objectives. The optimal combination of management decision can optimize company value that will affect shareholder wealth. The funding decision is a very significant decision for the company because it involves the acquisition of funding sources for operational act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Based on research conducted by Tanto (2019), found that investment decisions have a significant effect on firm value. The result of this study is also supported by Utami & Darmayanti (2018) and Putri & Yuliani (2018) that found investment decisions with positive and significant effect on firm value.…”
Section: Investment Decision and Firm Valuesupporting
confidence: 86%
See 3 more Smart Citations
“…Based on research conducted by Tanto (2019), found that investment decisions have a significant effect on firm value. The result of this study is also supported by Utami & Darmayanti (2018) and Putri & Yuliani (2018) that found investment decisions with positive and significant effect on firm value.…”
Section: Investment Decision and Firm Valuesupporting
confidence: 86%
“…Muharti and Anita's research (2017) stated that financing decisions have a positive effect on firm value. Furthermore, the research conducted by Putri, Isnurhadi & Yuliani (2018) said that financing decisions has a positive and significant effect on firm value.…”
Section: Financing Decision and Firm Valuementioning
confidence: 99%
See 2 more Smart Citations